STUDI KOMPARASI PENDEKATAN INQUIRY TIPE PROJECT BASED LEARNING DENGAN GROUP INVESTIGATION TERHADAP PEMAHAMAN KONSEP PELESTARIAN LINGKUNGAN HIDUP PADA VEGETASI MANGROVE DI KAWASAN PANTAI KARANGSONG - INDRAMAYU - Astriyandi, Asep Andri (Indonesia University of Education, 2016)
This study aims to improve understanding of the concept of students in learning geography through the implementation of project-type approach to inquiry based learning with group investigation, understanding the concept of indicators analyzed in this study is the aspect of translation, interpretation and extrapolation. The learning model is applied for in accordance with the principles of learning, which is centered on the problems, real experience, and students must have feedback about the process of achieving goals. Data obtained using quasi-experimental research methods, with techniques pretest and posstest. Research data processing techniques apply normality test and homogeneity test. To test the hypothesis, researchers applied statistical calculations parametric and non-parametric statistical calculations softwere utilization. The subjects were students of class XI and class XI IPS 2 IPS 3 SMAN 1 Anjatan. The results showed; (a) in the experimental class with the model PPA there are differences in pretest and posttest results, from the t-test results obtained sig (2-tailed) 0.000 0.05, (b) the experimental class with GI learning there are differences in pretest and posttest results , of the t-test results obtained sig (2-tailed) 0.000 0.05, (c) Generally from the comparison shows that the PPA models superior to models GI, it is based on the average - average class n.gain The PPA is superior, (d) Model PPA and GI have a different effect on every aspect of understanding the concept, the PPA is superior aspect is translation and interpretation, while GIs are superior in the aspect of translation and ekstrapolation. Thus the type of project-based inquiry approach to learning can be compared to the main alternative diajadikan group investigation in increasing understanding of the concept of students in learning geography, especially the matter of environmental preservation.Â Keywords: project based learning model, model group investigation,concept